Estimation of surgeons’ ergonomic dynamics with a structured light system during endoscopic surgery - Lobo, David; Anuarbe, Pedro; López‐Higuera, José Miguel; Viera, Jaime; Castillo, Nathalia; Megía, Roberto (International forum of allergy & rhinology, 2019)
Background The purpose of this study was to use motion capture to collect body posture information during simulated endoscopic sinus surgery interventions performed by both specialists and residents in standing and sitting positions and to analyze that information with the validated Rapid Upper Limb Assessment (RULA) tool, which allows calculation of a risk index of musculoskeletal overload. Methods Bilateral endoscopic sinus surgery was performed in 5 cadaver heads by 2 residents, and 4 practicing rhinologists. Musculoskeletal symptoms were evaluated before and after the dissection. Full‐body postural data were collected with the help of Kinect and a .NET WPF (Windows Presentation Foundation) software application to record images of the surgical procedures, and then analyzed with the RULA tool to calculate a risk score indicative of the exposure of the individual surgeon to ergonomic risk factors associated with upper extremity musculoskeletal disorders. Results All subjects reported physical discomfort after nasal endoscopic procedures. An overall similar RULA score was obtained by the residents and the practicing rhinologists. The RULA score was slightly lower for the sitting position than for the standing position, mostly due to a lower score in group B (neck, trunk, and leg); however, the RULA score for group A (arm and wrist analysis) was higher, denoting a higher risk for the upper back and arms. Conclusion Significant musculoskeletal symptoms were reported after an endoscopic operation by both the resident and the practicing otolaryngologists. All surgeons obtained a high RULA score, meaning that urgent changes are required in the task.